Influence of the Concentration of Water Droplets in an Aerosol Cloud on the Characteristics of their Collisional Interaction; Journal of Engineering Physics and Thermophysics; Vol. 93, iss. 2 - Vysokomornaya O. V. Olga Valeryevna; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Shlegel N. E. Nikita Evgenjevich (2020, 2020)
Title screen